Determination of Individuals’ Attitudes Toward COVID-19 Vaccines and Health Fatalism: A Cross-sectional Study from Turkey - Erkal, Emre; Demirkiran, Bedriye Cansu; Köleoğlu, Şerife; Demir Çam, Sevgi (Makara Journal of Health Research, 2023)
Background: Vaccines have positive effects on the course of epidemics. This study was conducted to determine individuals’ attitudes toward coronavirus disease-2019 (COVID-19) vaccines, their health fatalism, and factors affecting these. Methods: This cross-sectional study included 944 participants living in Turkey, who were included in the study by snowball sampling, one of the nonprobability random sampling methods. Participant information form, attitudes toward the COVID-19 vaccine scale, and religious health fatalism scale were used to collect the study data. Independent sample t-test, one-way analysis of variance and Pearson correlation analysis were used in the data analysis. Results: Participants had mean positive attitudes toward COVID-19 vaccine score of 3.63 ± 1.14, mean negative attitudes toward COVID-19 vaccine score of 3.44 ± 0.91, and mean health fatalism score of 45.75 ± 17.43. Negative and significant correlations were found between participants’ mean health fatalism score and their mean positive attitudes score (r = −0.213) and their mean negative attitude score (r = −0.362) (p < 0.001). Conclusions: Individuals were found to have high positive and low negative attitudes toward COVID-19 vaccines and moderate levels of health fatalism. Individuals with high health fatalism had low positive and high negative attitudes toward COVID-19 vaccines.